Comparison of the Mechanical Behaviour of Standard and Auxetic Foams by X‐ray Computed Tomography and Digital Volume Correlation. (13th September 2013) - Pierron, F.; McDonald, S. A.; Hollis, D.; Fu, J.; Withers, P. J.; Alderson, A.
ABSTRACT The tensile behaviour of standard and auxetic polyurethane foams are contrasted by digital volume correlation of 3D images collected by in situ X‐ray computed tomography (CT). It was found that subset sizes of 32 and 64 voxels for the auxetic and standard foams were optimal for strain resolutions in the order of 0.1%. For the standard foam, good uniformity of strain was observed at low strains giving a tangent Poisson's ratio of 0.5. Some heterogeneity of strain was observed at higher strains, which may be related to the fixtures. The behaviour of the auxetic foam was totally different, with strain being spatially heterogeneous with transverse strains both positive and negative but giving a negative Poisson's ratio on average. This suggests that the unfolding tendency of some groups of cells was higher than others because of the complex frozen starting microstructure. Further different methods of deriving Poisson's ratio gave different results. Besides revealing interesting microstuctural mechanisms of transverse straining, the study also shows digital volume correlation of tomography sequences to be the perfect tool to study complex mechanical behaviour of cellular materials.